Simultaneous topography-guided PRK followed by corneal collagen cross-linking after lamellar keratoplasty for keratoconus - Spadea L (Dove Medical Press, 2012)
Leopoldo Spadea,1 Marino Paroli21University of L’Aquila, Department of Biotechnological and Applied Clinical Sciences, Eye Clinic, L’Aquila, 2La Sapienza University, Department of Biotechnology and Medical-Surgical Sciences, Latina, ItalyBackground: The purpose of this paper is to report the results of using combined treatment of customized excimer laser-assisted photorefractive keratectomy (PRK) and prophylactic corneal collagen crosslinking (CXL) for residual refractive error in a group of patients who had previously undergone lamellar keratoplasty for keratoconus.Methods: The study included 14 eyes from 14 patients who had originally been treated for keratoconus in one eye by excimer laser-assisted lamellar keratoplasty (ELLK), and subsequently presented with residual ametropia (-6.11 D ± 2.48, range -2.50 to -9.50). After a mean 40.1 ± 12.4 months since ELLK they underwent combined simultaneous corneal regularization treatment with topographically guided transepithelial excimer laser PRK (central corneal regularization) and corneal CXL induced by riboflavin-ultraviolet A.Results: After a mean 15 ± 6.5 (range 6–24) months, all eyes gained at least one Snellen line of uncorrected distance visual acuity (range 1–10). No patient lost lines of corrected distance visual acuity, and four patients gained three lines of corrected distance visual acuity. Mean manifest refractive spherical equivalent was -0.79 ± 2.09 (range +1 to -3.0) D, and topographic keratometric astigmatism was 5.02 ± 2.93 (range 0.8–8.9) D. All the corneas remained clear (haze < 1).Conclusion: The combination of customized PRK and corneal CXL provided safe and effective results in the management of corneal regularization for refractive purposes after ELLK for keratoconus.Keywords: corneal collagen crosslinking, excimer laser-assisted lamellar keratoplasty, photorefractive keratectomy